The Integration of Islam and Science (An Analysis of the Problematics and Levels of Integration) - Ach. Maimun (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2021)
Lagging behind in the fields of science and technology is a problem that has emerged since the end of the Middle Ages (18th century AD), so that since then Muslims have been infected with "catching-up syndrome" which has caused negative responses and resistance from many groups. This is mainly due to theological concerns, cultural effects and ecological crises. At least the prominent resistance in the form of movements can be divided into three (1) restorationist movements, (2) Bucailis movements and (3) fundamentalist movements. The response to these efforts is counterproductive with efforts to catch up and at the same time with the spirit of Islam that upholds science. Therefore, a more basic study is needed on a proportional and harmonious integration integration framework. This can be done by incorporating Islamic values ​​that are principled without turning off the dynamic elements of science and technology, but can instead spur and direct them to the desired goal, the welfare of life. The integration of these values ​​touches three levels (1) the level of scientific mental development, which consists of: (a) encouragement to study nature, (2) positive appreciation and awarding of scientific activities and (c) presentation of scientific character. (2) The level of world view, namely establishing an Islamic world view of the universe such as (a) recognition of the existence of God as the creator and preserver of nature, (b) belief in non-physical reality and not just physical-empirical reality, (c) acknowledgment of the existence of the purpose of the universe and (d) recognition of the existence of a moral order for the universe. (3) Orientation level, which includes: (a) epistemic orientation, namely empirical truth that can lead to strengthening faith and closeness to God and (b) practical orientation in the form of technological application by affirming that the purpose of applying science is humanity and universal prosperity that related to the role of humans as Khalifah.